Analysis of the Influence of Tourism Product Attributes, Prices and Promotions on Tourist Visiting Decisions at Pintu Langit Prigen Pasuruan Tourism Object: Analisis Pengaruh Atribut Produk Wisata, Harga Dan Promosi Terhadap Keputusan Berkunjung Wisatawan Di Objek Wisata Pintu Langit Prigen Pasuruan - Miranda Oqtaviani; As'at Rizal (Academia Open, 2021)
This study aims to determine the effect of tourism product attributes, prices and promotions on the decision to visit tourists at the Pintu Langit Prigen Pasuruan tourist attraction. This research includes quantitative research with data collection techniques, namely by distributing questionnaires to 100 respondents who are visitors to the Prigen Pasuruan Gate tour. The analytical technique used in this research is multiple linear regression analysis using SPSS (Statistical Program for Social Science) version 18 for windows. The results of this study prove that the attribute variable of tourism products affects the decision to visit, the price variable affects the decision to visit, the promotion variable affects the decision to visit tourists at the Pintu Langit tourist attraction, Prigen Pasuruan.